2006
DOI: 10.1074/jbc.m606483200
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Response of the Yeast Na+-ATPase ENA1 Gene to Alkaline Stress Involves Three Main Signaling Pathways

Abstract: Adaptive response of the yeast Saccharomyces cerevisiae to environmental alkalinization results in remodeling of gene expression. A key target is the gene ENA1, encoding a Na ؉ -ATPase, whose induction by alkaline pH has been shown to involve calcineurin and the Rim101/Nrg1 pathway. Previous functional analysis of the ENA1 promoter revealed a calcineurin-independent pH responsive region (ARR2, 83 nucleotides). We restrict here this response to a small (42 nucleotides) ARR2 5-region, named MCIR (minimum calcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
118
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 50 publications
8
118
0
1
Order By: Relevance
“…We found that the genes MGG_01822 (MoHOG1) and MGG_10268 (MoPBS2) were significantly upregulated when subjected to salt stress, which is in accordance with functions published already regarding osmotic stress regulation either in yeast [9] or M. oryzae [4,10]. Further evidence is given by genes predicted to encode homologues to the yeast ATPase ENA2 (YDR039C), which is involved in salt tolerance [8,16] or even a group of genes involved in stress-induced transport mechanisms (Tab. S1).…”
Section: Short Communicationsupporting
confidence: 89%
“…We found that the genes MGG_01822 (MoHOG1) and MGG_10268 (MoPBS2) were significantly upregulated when subjected to salt stress, which is in accordance with functions published already regarding osmotic stress regulation either in yeast [9] or M. oryzae [4,10]. Further evidence is given by genes predicted to encode homologues to the yeast ATPase ENA2 (YDR039C), which is involved in salt tolerance [8,16] or even a group of genes involved in stress-induced transport mechanisms (Tab. S1).…”
Section: Short Communicationsupporting
confidence: 89%
“…The involvement of Snf1 and Nrg1 in the transcriptional regulation of ENA1, a gene that is known to respond to saline and alkaline stress (Alepuz et al, 1997;Lamb et al, 2001;Platara et al, 2006), was suggestive of saline-related transcriptional regulation of NSF1. Interestingly, the transcription of NSF1 has been reported to increase slightly when cells are treated with 0.8 M NaCl (Yoshimoto et al, 2002).…”
Section: Ena1 Transcriptional Activation Is Partially Nsf1-dependentmentioning
confidence: 99%
“…The transcription of ENA1 is activated under nonfermentable carbon conditions, saline stress and alkaline stress (Alepuz et al, 1997;Cyert, 2003;Lamb et al, 2001;Platara et al, 2006). To analyse the potential involvement of Nsf1 in the transcriptional activation of ENA1, we cultured pKC201 (ENA1-lacZ) transformants of the wild-type and nsf1D mutant strains in selective synthetic glucose media to exponential phase before shifting the cells to salt-stress conditions (see Methods).…”
Section: Ena1 Transcriptional Activation Is Partially Nsf1-dependentmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we have chosen a well-established perturbation model, the exposure of yeast cells to an abrupt increase in external pH. Previous DNA microarray-based analyses of the effect of this perturbation on gene expression remodeling have shown that it results in several hundred of genes being induced or repressed (Lamb and Mitchell, 2003;Lamb et al, 2001;Platara et al, 2006;Ruiz et al, 2008;Serrano et al, 2002Serrano et al, , 2006Viladevall et al, 2004), as a result of the modulation of diverse signaling pathways (for a recent review, see Arino, 2010). In this work we present a comparison of the transcriptional changes detected after short-term (10 min) exposure to high pH stress (pH = 8.0) for both wildtype and snf1 mutant strains.…”
mentioning
confidence: 99%